Impact of age at diagnosis on disease progression in patients with primary sclerosing cholangitis - Rupp, Christian; Rößler, Alexander Fritz; Rauber, Conrad; Friedrich, Kilian; Wannhoff, Andreas; Weiss, Karl Heinz; Sauer, Peter; Schirmacher, Peter; Süsal, Caner; Stremmel, Wolfgang; Gotthardt, Daniel (United european gastroenterology journal, 2018)
BackgroundThe median age of diagnosis of primary sclerosing cholangitis (PSC) is ?30?40 years.ObjectiveWe aimed to analyse disease progression and liver-dependent survival in patients diagnosed with PSC after 50 years of age.MethodsPatients with PSC were analysed with regard to their age at diagnosis. Patients with a first diagnosis of PSC after the age of 50 years were considered as the late-onset group.ResultsA total of 32/215 (14.9%) patients were diagnosed with PSC after 50 years of age. The proportion of females was significantly higher among patients with late-onset PSC (48.4 vs. 27.3%; p?=?0.02). Patients with later diagnosis required dilatation therapy more often due to dominant stenosis (84.2 vs. 53.1%; p?=?0.01) and suffered from recurrent cholangitis more often (48.3 vs. 21.0%; p?=?0.003). Patients with late-onset PSC had reduced transplantation-free survival (10.5?±?0.6 years vs. 20.8?±?1.7 years, p?
First Published June 17, 2017
Gesehen am 03.05.2019